Detection of Antinuclear Antibodies in HIV-Infected Individuals - Promsawan, Kanyanee; Klangsinsirikul, Phennapha; Dettrairat, Sakchai; Pornprasert, Sakorn; Anukul, Nampeung; Chairatanapiwong, Saowanit; Sirikul, Chonticha; Louthrenoo, Worawit; Leetrakool, Nipapan; Pultajuk, Unchalee; Singboottra, Panthong (Journal of Associated Medical Sciences, 2017)
Background: The causes of autoimmune diseases (ADs) are still not clearly known, but it is believed that diseases are propelled by multiple factors including genetic, hormone and environmental factors. For the environmental factors that trigger ADs, infection is one of the important factor. In the present study, we seek to disclose whether HIV infection instigate autoimmune diseases. Objectives: To investigate the proportion of antinuclear antibodies (ANA)-positive persons in HIV-infected patients. Materials and methods: Blood samples were obtained from 76 HIV-infected patients and 100 healthy donors. Separated plasma from these samples were subjected to the ANA analysis by indirect immunofluorescent assay. Results: A positive-ANA test was detected in 25% and 22% from HIV-infected patients and healthy blood donors, respectively. The ANA-positive result in female healthy donors tends to be higher than that of a male group, whereas the ANA-positive result in males seemed to be higher in HIV-infected patients, assuming that sex hormone may play some notable roles in altering an immune response to favor an autoimmunity. Moreover, high ANA-positive proportion was found in the oldest subject group and in HIV-infected patients the highest ANA-positive proportion was found in the group with the longest infection duration, assuming that age and chronic infection may also involve in ANA production. Conclusion: Though the proportion of HIV-infected patients who had ANA positive results was not statistically significant different when compared to that of healthy blood donors, the tendency of the proportion seems to be higher in HIV-infected group. The highest proportion was found in the patients with the longest infection duration. Therefore, it could be suspected that chronic HIV infection might be associated with ANA production.